In vitro Study of Five Herbs Used Against Microbial Infections in Burundi. (17th August 2017) - Ngezahayo, Jérémie; Ribeiro, Sofia Oliveira; Fontaine, Véronique; Hari, Léonard; Stévigny, Caroline; Duez, Pierre
Abstract : The emergence of antimicrobial resistant infectious diseases remains a major threat to worldwide public health, in developed and in developing countries. Therefore, new antimicrobial agents acting by new mechanisms of action are urgently needed. As plants used in traditional medicine may help to overcome these problems, Justicia subsessilis, Platostoma rotundifolium, Pavetta ternifolia, Stomatanthes africanus, and Virectaria major (plants highly cited to be used against microbial infections in traditional Burundian medicine) were studied to assess their traditional use efficacy. We conducted a preliminary phytochemical screening of the extracts, as well as their direct and indirect (effect on antibiotic resistance) antibacterial activity on four bacterial strains ( Staphylococcus sp. and Escherichia coli ) by broth microdilution methods. All five medicinal plants investigated in this work were found to have direct antibacterial activity against all tested bacterial strains (minimum inhibitory concentration = 62.5–1000 μg/mL) that may support the use of these species in traditional Burundian medicine. Extracts (with no direct antibacterial activity), tested at 200 μg/mL, decreased the MIC values of β‐lactams and aminoglycoside antibiotics by a factor of 2 to 64‐fold. These interactions between plant extracts and antibiotics could open an avenue of research against antibiotic resistance. Copyright © 2017 John Wiley & Sons, Ltd.